The Criminal Enforcement Of The Fraud Mode Of Multiple Money (Case study Decision No.61 / Pid.B / 2019 / PN.Blora) - Sumaryono Sumaryono; Sri Kusriyah Kusriyah (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
Fraudulent criminal acts that have been regulated in the Criminal Code (KUHP) with various modes, one of which is fraud by shamans with a multiplied money mode has made law enforcers increasingly have to rack their brains to be able to prove it. This study aims to examine and analyze law enforcement by the judge in decision No.61 / Pid.B / 2019 / PN.Blora with consideration of the criminal elements. The research method used is a sociological juridical approach. The specifications of the study were conducted using descriptive analytical methods. The data used for this study are primary and secondary data. The data consists of primary data and secondary data using field research methods, interviews, and literature studies. Based on the research it was concluded that the case ruling number 61 / Pid.B / 2019 / PN Bla with a fraud case with shamanism practices in the mode of duplicating the judge's money considering that the Defendants have been indicted by the Public Prosecutor with alternative indictments, so the Panel of Judges paid attention to the facts The aforementioned law decides on the first alternative indictment as regulated in Article 378 of the Criminal Code Jo Article 55 paragraph (1) of the 1st Criminal Code by considering the elements of that article.Keywords: Criminal Law Enforcement; Fraud; Multiple Money.